Urine Results as A Predictor of Acute Kidney Failure after Radical Cystectomy and Ureterocutia Stoma - Iwan, Iwan; Majid, Abdul; Fitriani, Lya (Indonesian Journal of Global Health Research, 2024)
Acute kidney failure (AKI) is a spectrum of diseases characterized by changes in urine production and serum creatinine concentration. In recent years the concept of kidney injury and failure has evolved, replacing the term "acute kidney failure" (GGA) with the criteria of Risk, Injury, Failure, Loss of kidney function, and end-stage kidney disease, where healthcare workers must assist patients in self-management to improve their well-being and prolong life. One of the self-management is adherence to fluid restriction and diet which is very important to reduce the incidence of deterioration of the patient's condition, Cuterostomy (CU) is a rare form of urination diversion, but can be the simplest urine diversion option in high-risk elderly patients. Objective to determine the amount of urine output as a predictor of renal failure I post-radical surgery cystectomy and ureterocutaneous stomas. An intervention was carried out starting on the 2nd day after surgery and a sample of one patient with a diagnosis of acute kidney failure after radical cystectomy and ureteroduct stoma surgery who was temporarily undergoing treatment in the urology room of Lontara 4 Wahidin Sudirohusodo Hospital Makassar, the intervention provided was monitoring urine production, increasing urea, creatinine and GFR in postoperative patients with radical cystectomy and ureterocutaneous stoma for 6 days from from April 22 to April 27, 2024 by means of urine production in 24 hours which is accommodated in a stoma bag measured using a 2-liter urine measuring cup and the results of urine voleme in 24 hours are recorded on the integration sheet, urea and creatinine levels are observed every 2 days by taking blood samples and examined in the laboratory of Wahidin Sudirohusodo Hospital. After postoperative radical cystectomy and ureterocular stoma monitoring intervention, there was an increase in urine volume every day and did not have a significant impact on the improvement of urea, creatinine and GFR in acute renal failure. Conclusion: after the intervention, there was an improvement in urea, creatinine and GFR levels but it was not very meaningful for patients with acute kidney failure, namely radical cystectomy and ureterocant stoma which were shown by signs of improvement with an increase in urine volume every day.